Kesesuaian Buku Teks Pelajaran IPA Kelas IX Semester 2 dengan Tujuan Kurikulum dan Peluang Pengintegrasian Materi Tanah Longsor - Rima Cemani; Ahmad Fauzi; Hamdi Rifai (Universitas Negeri Padang, 2018)
This study aims to determine the level of suitability of science materials with curriculum objectives in textbooks for junior high school in grade IX semester 2 and to determine the suitability of science materials in class IX textbooks for science junior high school with landslide material.This research is a descriptive research with a qualitative approach. The population of the data in this study is all grade IX textbooks of junior high school science lessons published in Indonesia in semester 2 and the data samples in this study are class IX textbooks of semester 2 published by Ministry of Education and Culture 2015, Yudhistira and Erlangga. The data in this study were taken using research instruments and data collection techniques through documentation studies. The suitability percentage of science materials with curriculum objectives in the 2nd semester in the textbooks published by the Ministry of Education and Culture is 80% in the appropriate category, then the percentage of suitability of science materials with curriculum objectives in the textbooks published by Yudhistira is 76% with appropriate categories and the percentage of suitability of the Natural Science material with the purpose of the textbook curriculum published by Erlangga is 74% with a category that is appropriate. Then the suitability level of science material for grade IX in semester 2 with landslide material is 29% with an inappropriate category. Science material for grade IX semester 2 is not suitable for integration with Landslide material.